Carlsson mot May : Om mottagandet av Jan Troells Sagolandet - Hedling, Olof (Filmhäftet, 1993)
On the Swedish reception of Jan Troell's documentary Sagolandet (The Fairy land, 1989).
Keywords: Documentary; political film; political hegemony; pictures of Sweden